URGENSI CHARACTER BUILDING SEBAGAI USAHA PERWUJUDAN INSAN YANG UNGGUL - I Made Ariasa Giri (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Education and character coaching of the nation has a great role to advance the civilization of the nation in order to become an increasingly advanced nation with knowledgeable, insightful and characterful Human Resources. Maintaining the identity and character of the nation is a reflection of the attitude that becomes the identity of the nation that can give birth to people of good character, advancing our nation's civilization is getting ahead with a quality and characterful human resources. Given the importance and breadth of the scope of the nation's character development in order to maintain the identity of the nation from the sway of the globalization flow, it is necessary to commit and support from state organizing agencies, business and industry, communities, mass media and other stakeholders to develop work programs and coordinate with related parties in order for strong synergy to realize a better Indonesia.